Maintenance of multipotency of bone marrow mesenchymal stem cells on poly(ε-caprolactone) nanoneedle arrays through the enhancement of cell-cell interaction - Ren, Xiaoxue; Gao, Xiaoting; Cheng, Yicheng; Xie, Lingxia; Tong, Liping; Li, Wei; Chu, Paul K.; Wang, Huaiyu (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stem cells (MSCs), with high self-renewal ability and multipotency, are commonly used as the seed cells for tissue engineering. However, the reduction and loss of multipotential ability after necessary expansion in vitro set up a heavy obstacle to the clinical application of MSCs. Here in this study, we exploit the autologous crystallization ability of biocompatible poly (ε-caprolactone) (PCL) to obtain uniformly distributed nanoneedle arrays. By controlling the molecular weight of PCL, nanoneedle with a width of 2 μm and height of 50 nm, 80 nm and 100 nm can be successfully fabricated. After surface chemical modification with polydopamine (PDA), the water contact angle of the fabricated PCL nanoneedle arrays are reduced from 84° to almost 60° with no significant change of the nanostructure. All the fabricated substrates are cultured with bone marrow MSCs (BMMSCs), and the adhesion, spreading, proliferation ability and multipotency of cells on different substrates are investigated. Compared with the BMMSCs cultured on pure PCL nanoneedle arrays, the decoration of PDA can improve the adhesion and spreading of cells and further change them from aggregated distribution to laminar distribution. Nevertheless, the laminar distribution of cultured cells leads to a week cell-cell interaction, and hence the multipotency of BMMSCs cultured on the PCL-PDA substrates is decimated. On the contrary, the pure PCL nanoneedle arrays can be used to maintain the multipotency of BMMSCs via clustered growth, and the PCL1 nanoneedle array with a height of 50 nm is more promising than the other 2 with regard to the highest proliferation rate and best multipotential differentiation ability of cultured cells. Interestingly, there is a positive correlation between the strength of cell-cell interaction and the multipotency of stem cells in vitro. In conclusion, we have successfully maintained the multipotency of BMMSCs by using the PCL nanoneedle arrays, especially the PCL1 nanoneedle array with a height of 50 nm, as the substrates for in vitro extension, and further revealed the importance of cell-cell interaction on the multipotency of MSCs. The study provides a theoretical basis for the behavioral regulation of MSCs, and is instructive to the design of tissue engineering scaffolds.